Analisis Kepuasan Pengguna Aplikasi BRImo Menggunakan Metode End User Computing Satisfaction dan Delone & Mclean - Harmutika, Della; Rahmawita, Medyantiwi; Rozanda, Nesdi Evrilyan; Zarnelly, Zarnelly (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
BRImo is a mobile banking application that provides online transaction services, but there are still some BRImo users who are still constrained by using the BRImo application. As for difficulties in using the BRImo application, difficulty transacting, difficulty logging in, then users are often blocked which results in less comfort in using the BRImo applicationn which can reduce the level off user trust. The goal is to find out the level of user satisfation of the BRImo application usingg the End User Computing Satisfaction (EUCS) and Delone & Mclean research models. The EUCS model means a comparison model between reality and expectations (reality). DeLone and McLean means a model for identifying factors that cause the success of an information system. In this study, it can be measured from 5 EUCS indicators and 3 Delone & McLean indicators which will use purposive sampling techniques collected through online questionnaires in the form of google forms to 100 user respondents, so that the data obtained will be analyzed using SmartPLS 4. Thus the final resultss of this study state that the variables of content, easy of use, information quality, service quality, and timeliness have a significant effect, then 3 other variables, namely accuracy, format, and system quality, do not have significant positive effect on the satisfaction of BRImo application users.